Pengaruh Emphaty, Tangible, Responsiveness, Kedisiplinan Pegawai Terhadap Kepuasan Masyarakat di Pemerintahan Desa - Hadi, Nor; Tarwan, Ode (BISNIS, 2018)
This article explains the results of empirical testing of the theory of total quality service, that service quality in this study with tangible, responsiveness, empathetic, and disciplinary variables determines the level of community satisfaction. The concept is in line with the new paradigm in the management of government institutions, including the village government as outlined in the policy of Bureaucratic Reform. The study was conducted at the village government service office in Masohi District, Central Maluku. The number of respondents are 40 people, with a response rate of 95%. The survey was conducted by distributing questionnaires, namely researchers directly to the research location to spread questionnaires. Data is analyzed by using regression. The results showed that based on alpha 5% the empathetic, tangible and disciplined variables had a significant positive effect. Meanwhile, the responsiveness variable shows no significant effect. The results of this study mean that even though responsiveness does not have a significant effect, but see the value of R square 0.892 means that all independent variables can explain as much as 89% of the dependent variable.